CONTEMPORARY MIGRATORY MOVEMENTS IN THE MUNICIPALITY OF TRSTENIK - Milosavljević, Saša (Bulletin of Natural Sciences Research, 2018)
Municipality of Trstenik located in spacious valley of  Zapadna Morava, has always provided favorable conditions for the settlement of the population and the development of settlements. After the World War II, there was a need for recruiting a large number of people because of a huge development of metal industry in Trstenik, and that fact attract the immigrants from the area of Rasina, Aleksandrovačka Župa, Podibra, Lepenica, Levač and Temnić. The ratio between autochthonous and migrant population according to 1961 Census was 69%:31%, while the same ratio for the 2011 census was 59%:41%. Nearly  a quarter (24%) of total number of immigrants immigrated in the inter-census period from 1981. to 1991, and almost all (94% of immigrants) immigrated  from the same area of the republic. The process of emigration particularly intensified in the early nineties of the XX century when young and highly educated population emigrate, and the main reason for that was a poor economic situation.
Keywords: populations; migrations; Trstenik; Serbia